1962
DOI: 10.1128/aem.10.2.157-168.1962
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Biosynthesis of Streptomycin

Abstract: 1962. iMyo-inositol, especially in combination with arginine, enhances streptomycin production. Compounds which show structural relationship with myo-inositol are ineffective. Myo-inositol decreases the incorporation of CI4-glucose into streptomycin, particularly into streptidine. This effect suggests that myo-inositol is a precursor of the streptidine ring. Methionine stimulates antibiotic production in a synthetic medium but proves to be unfavorable in a complex medium. The y-and S-isomers of hexachlorocyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1963
1963
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Glucose stimulates production and retards lysis of such suspensions. Like the complete fermentation, resting-cell synthesis is susceptible to inhibition by inorganic phosphate (75,103), although a low level such as 5 X 10-4 M stimulates production (85).…”
Section: Downloaded Frommentioning
confidence: 99%
See 3 more Smart Citations
“…Glucose stimulates production and retards lysis of such suspensions. Like the complete fermentation, resting-cell synthesis is susceptible to inhibition by inorganic phosphate (75,103), although a low level such as 5 X 10-4 M stimulates production (85).…”
Section: Downloaded Frommentioning
confidence: 99%
“…The two amidino groups attached to the streptamine nitrogens are derived by transamidination from arginine. With some strains, addition of arginine and inositol to fermentation media increases streptomycin yields (35,42,72,75,86,111); streptidine has also been reported to stimulate production (86). Synthesis of streptomycin by washed suspensions may also be stimulated by arginine and inositol and by streptidine or streptobiosamine (75,85).…”
Section: Biosynthesis Of the Streptidine Moietymentioning
confidence: 99%
See 2 more Smart Citations
“…In the production of streptomycin, arginine and inositol were found to exert a stimulating effect (Saunders, 1950;Severina, Gorskaya, and Gracheva, 1959;Egorov, 1959;Galanina and Agatov, 1959;Majumdar and Kutzner, 1962a). NMajumdar and Kutzner (1962a) reported that these compounds stimulated streptomycin production of the same culture used by me as the original culture.…”
Section: Resultsmentioning
confidence: 99%